Modified Reciprocal Teaching: Cooperative Learning Technique for Enhancing Communication Skills of First Year Engineering Students - Kadam, Dipali M.; Sawant, Supriya Y. (Journal of Engineering Education Transformations, 2020)
With the advancement of technology and globalization, Communication skills as a life-long learning skill is an essential component in engineering education. Communication is one of 12 graduate attributes, defined by ABET (Accreditation Board for Engineering and Technology). The engineering classroom is currently experiencing a shift from teacher-centred teaching where teacher focused on what they are teaching, to studentcentred learning through innovative teaching-learning techniques. Active learning has become a significant process in outcome-based education (OBE). It comprises various approaches such as cooperative and collaborative learning techniques, PBL (problem/project/puzzle-based Learning), TBL (Task based learning), Peer instructions, T-P-S (Think-Pair-Share), Flipped Classroom and Reciprocal Teaching and many others. The Reciprocal Teaching is an instructional strategy specially designed for comprehension purpose. The present work offers some insights after successful implementation of modified reciprocal teaching for improving communication skills of First Year B. Tech. students at Kasegaon Education Society’s Rajarambapu Institute of Technology, Rajaramnagar (RIT). It was an attempt to develop all four basic language skills: Listening, Speaking, Reading and Writing. This research was conducted for four weeks during practical sessions. After successful implementation the students of experimental group were assessed by qualitative and quantitative methods. The results reflected increase in CO attainment of experimental group as compared to control group. The structured implementation of modified reciprocal teaching as an active learning tool helped to enhance students’ presentation skills, team work, leadership skills, and ultimately communication skills.